2005
DOI: 10.1016/j.parkreldis.2005.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of effort during handgrip and tongue elevation in Parkinson's disease

Abstract: Background-Fatigue and the accompanying perception of effort are often heightened in Parkinson's disease.Objectives-To compare performance on three sense-of-effort tasks between patients with PD and matched neurologically normal control subjects.Methods-Sixteen PD subjects and 16 normal subjects performed three tasks to assess sense of effort: self-ratings of effort using direct-magnitude estimation, generating pressures at various levels of effort, and sustaining a submaximal level of effort. The latter two t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 38 publications
3
30
0
Order By: Relevance
“…goal that remains somewhat constant and is based not on an absolute value but rather one that is proportional to an individual's physiologic range. Speech is a low-force task, and work by Solomon and Robin (2005) has indicated that the perception of effort during tongue movements (nonspeech in this case) relative to pressure generation was more sensitive at the extremes of the effort range. That is, the tongue may be more sensitive to effort differences at the low (and high) end of the tongue pressure physiologic range, allowing for a %Max target to be reliably attained.…”
Section: Lacp-sp As a Percentage Of Lacp-max (%Max)mentioning
confidence: 82%
“…goal that remains somewhat constant and is based not on an absolute value but rather one that is proportional to an individual's physiologic range. Speech is a low-force task, and work by Solomon and Robin (2005) has indicated that the perception of effort during tongue movements (nonspeech in this case) relative to pressure generation was more sensitive at the extremes of the effort range. That is, the tongue may be more sensitive to effort differences at the low (and high) end of the tongue pressure physiologic range, allowing for a %Max target to be reliably attained.…”
Section: Lacp-sp As a Percentage Of Lacp-max (%Max)mentioning
confidence: 82%
“…Fatigue is a common complaint in disease states such as Parkinson's disease (PD), various cancers, autoimmune disorders, and viral infections (7,18,20,32) and may be associated with increased levels of IL-1␤. This cytokine has been shown to be elevated in the brains of subjects with PD (22), and IL-1␤ appears to be involved with cachexia associated with various cancers (13).…”
Section: Discussionmentioning
confidence: 99%
“…It is portable and easy to use, is noninvasive, and presents fast, accurate, and reliable measurements (4)(5)(6) . After that, many studies proposed to measure the pressure made by the tongue on the oral cavity (7) during functions such as speech (8) , swallowing, (5) and chewing (9) ; at rest (10) ; and during the maximum isometric contraction for comparing with different portions of the tongue (anterior and dorsum) among young adults (11) . The pressure of the tongue has also been studied in relation to gender (11)(12)(13)(14) and age (5,(13)(14)(15) in individuals diagnosed with obstructive sleep apnea (16) , neurological conditions (17) , and disorders in the head and neck area (18) .…”
Section: Introductionmentioning
confidence: 99%